Innovation Risks as an Important Element of Risk Management - Safarova, G.N. (Herald of Azerbaijan Engineering Academy, 2024)
The article examines the impact of risks, especially innovation risks, on the effectiveness of innovative activities of enterprises. The reasons for the emergence of innovative risks and their dependence on various factors were also considered, and the expediency of taking measures aimed at identifying and gradually reducing the risks of an innovative project was noted. Attention was also drawn to the need to apply a synergistic approach based on "risk management" to identify and manage the level of innovation risks in the face of uncertainty.